Sustainability of traditional motifs in Malaysian batik block / Rabiatuadawiyah Mohd Kari, Mohd Azhar Samin and Rafeah Legino - Mohd Kari, Rabiatuadawiyah; Samin, Mohd Azhar; Legino, Rafeah (Universiti Teknologi MARA, 2018)
The history of batik block in Malaysia began in 1911 at Kota Bharu, Kelantan. Batik block is produced by using hot (melted) wax on a copper block. The motifs of batik block, which portray local identities, have already been around since the 20th century. Later, these motifs have underwent a transformation, whereby the block producers no longer used designs which reflected traditional styles and identities. As such, modern batik block in Malaysia does not have a strong identity. With respect to this problem, one of the objectives of this study was to analyse the various types of the local batik block designs in terms of their local characteristics. Therefore, interviews have been conducted via typological analysis. To achieve the same, guidelines for the designing of batik block need to be introduced. This research is expected to create awareness regarding the importance of the identities of batik block, and the outcomes of the standard will act as references for batik block producers and universities in the future.